Справочные материалы для сварщиков - Никитин В. П.; Николаев Г. А.; Лехциер И. Р.; Бринберг И. Л.; Гельман А. С.; Евсеев Ю. Б.; Рыкалич Н. Н.; Фриндлянд Л. А.; Ерохин А. А.; Любавский К. В.; Таубер Б. А. (Москва, Машгиз, 1951)
Авторы указ. на обороте тит. листа